Sosyal sermaye bağlamında bölüm memnuniyeti ve sosyal ağ olarak okul ortamına bakış ilişkisi: İlahiyat fakülteleri örneği - Ali İnan (Türkiye Din Eğitimi Araştırmaları Dergisi)
Sense of belonging and social networks are recognized as important elements of social capital. It is stated in the literature that the satisfaction levels of individuals with their environments are related to their belonging levels. In a sense, the sense of satisfaction affects the sense of belonging, and the sense of belonging affects the view of social networks. The quality of these relations also contributes to the level of social capital. In this research on theology faculty students, the effect of the students' level of satisfaction with the department on their views about the school environment which constitutes the biggest social network of the university students was discussed. In this study, quantitative research method was used. The questionnaire used in the study was applied to the students studying in the Theology faculties of Ankara, Atatürk, Dicle and Dokuz Eylül universities that are selected through purposive sampling. According to the findings, a statistically significant difference was found in the expressing their thoughts freely in their schools and with mutual trust between their friends at school in terms of the level of satisfaction of university students with the department they study. In a sense, it was observed that department satisfaction factor of the students of Theology Faculty has an effect on their view of school environment.